(untitled) (Global Journal of Management and Business Research, 2023)
Inventory management is a very important and vital part of any kind of production business because an efficient supply chain depends on mostly proper inventory management In any mega construction project inventory management is more critical for binding international standard rules and regulations and also for containing different characteristics of the project The main objective of this paper is to study the existing research on inventory management find existing challenging factors that indicate poor performance of inventory management and also find better tools and techniques practices that create overall value for the project This research paper will be helpful for the construction industry and get guidelines for better inventory management